Strength and ductility with {10͞11} — {10͞12} double twinning in a magnesium alloy - M. Lentz (Nature Portfolio, 2016)
Double twins are thought to lead to premature failure of magnesium alloys. Here, the authors show that a magnesium-lithium alloy achieves the same compression failure strains with double twins as without, potentially generating strengthening through intra-granular networks of double twins.